1993
DOI: 10.1111/j.1600-051x.1993.tb00374.x
|View full text |Cite
|
Sign up to set email alerts
|

Dentin demineralization

Abstract: Preliminary work has shown that the rate of dentin demineralization increases with increasing concentrations of citric acid. This rate subsequently diminishes at much higher concentrations. The purpose of this study was to more precisely identify the citric acid concentration which produces peak dentin demineralization and to determine if this demineralization process is time dependent. Flat dentin surfaces were prepared on the buccal and lingual sides of 15 bovine molars. 8 depressions were made in each denti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 44 publications
2
26
1
5
Order By: Relevance
“…Thus, the available evidence indicates that the application of higher volumes of citric acid over 1 minute improves efficacy in removing the smear layer. Sterrett et al (38) showed that the effect of 10% citric acid on dentin demineralization was time dependent at 1, 2, and 3 minutes but was ineffective in removing the smear layer. Thus, the application of citric acid concentration higher than 42% for shorter times could improve apical third cleanliness.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the available evidence indicates that the application of higher volumes of citric acid over 1 minute improves efficacy in removing the smear layer. Sterrett et al (38) showed that the effect of 10% citric acid on dentin demineralization was time dependent at 1, 2, and 3 minutes but was ineffective in removing the smear layer. Thus, the application of citric acid concentration higher than 42% for shorter times could improve apical third cleanliness.…”
Section: Discussionmentioning
confidence: 99%
“…O ácido cítrico foi aplicado nas superfícies com bolinhas de algodão embebidas na solução por três minutos como preconizado por Sterett 26 , RosaWen 20 e Hawkins 12 , e pudemos observar que este condicionante foi efetivo na remoção do "smear layer" tanto sobre cemento quanto sobre a dentina e ainda observou-se outro efeito positivo: o ácido desmineralizou parcialmente um pequeno cálculo sub-clínico deixado na raspagem. Sabe-se que a raspagem, por mais criteriosa que seja, não é perfeita, e se o condicionamento remove estes pequenos cálculos que foram deixados, em concordância com Tanaka 27 podemos afirmar que este é outro benefício do condicionamento radicular.…”
Section: Discussionunclassified
“…Várias substâncias ácidas tem sido testadas com esse propósito, sendo o ácido cítrico pH 1 por 3 minutos, um dos protocolos mais empregados (STERRETT, BANKEY, MURPHY, 1993;AMARAL et al, 2011). A desmineralização de tecidos duros expõe colágeno e proteoglicanas associadas (BERGENHOLTZ, BABAY, 1998;RUGGERI et al, 2007) que são quimioatrativas para células mesenquimais (WIKESJO, NILVEUS, SELVIG, 1992).…”
Section: Desmineralização Dos Tecidos Durosunclassified
“…Agentes químicos desmineralizantes para superfície de tecidos duros têm sido amplamente documentados como biomodificadores de dentina e cemento, visando a potencializar os processos reparativos em tratamentos de defeitos periodontais, na dependência da liberação de fatores que atuam na cicatrização periodontal e na criação de um substrato que privilegia a seleção de células nos eventos de reparação (REGISTER, BURDICK, 1975; WIKESJÖ, NILVEUS, SELVIG, 1992;STERRETT, BANKEY, MURPHY, 1993;MARIOTTI, 2003;AMARAL et al, 2011;SILVA et al, 2016). Os agentes mais utilizados para este fim são o ácido cítrico (GARRETT, CRIGGER, EGELBERG, 1978), tetraciclina (TERRANOVA, MARTIN, 1982;ISIK et al, 2000;SCHWARTZ et al, 2000) e EDTA (BLOMLOF, LINDSKOG, 1995;BLOMLOF, BLOMLOF, LINDSKOG, 1996).…”
Section: Introductionunclassified